1996
DOI: 10.1128/jcm.34.8.1963-1969.1996
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive properties and antibiotic resistance of Klebsiella, Enterobacter, and Serratia clinical isolates involved in nosocomial infections

Abstract: Intestinal colonization by Klebsiella, Enterobacter, and Serratia (KES) strains is a crucial step in the development of nosocomial infections. We studied the adhesive properties, antibiotic resistance, and involvement in colonization or infection of 103 KES clinical isolates: 30 Klebsiella pneumoniae (29%), 16 Klebsiella oxytoca (15%), 30 Enterobacter aerogenes (29%), 14 Enterobacter cloacae (14%), and 13 Serratia sp. (13%) isolates. Half of them were resistant to several antimicrobial agents, including aminog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 24 publications
1
39
0
2
Order By: Relevance
“…Other studies demonstrated the influence of capsule and extended-spectrum beta-lactamase encoding plasmids upon K. pneumoniae adhesion (Hennequin and Forestier, 2007). A high prevalence of type 1 and type 3 pili has been previously observed in clinical and environmental K. pneumoniae isolates (Livrelli et al, 1996;Martynenko et al, 1992;Podschun et al, 2001;Schurtz et al, 1994). Type 3 pili, mostly found in K.…”
Section: Discussionmentioning
confidence: 80%
“…Other studies demonstrated the influence of capsule and extended-spectrum beta-lactamase encoding plasmids upon K. pneumoniae adhesion (Hennequin and Forestier, 2007). A high prevalence of type 1 and type 3 pili has been previously observed in clinical and environmental K. pneumoniae isolates (Livrelli et al, 1996;Martynenko et al, 1992;Podschun et al, 2001;Schurtz et al, 1994). Type 3 pili, mostly found in K.…”
Section: Discussionmentioning
confidence: 80%
“…It is likely that the strains in which the fimbrial genes were detected but where fimbrial expression was not seen are able to express the fimbriae but do not do so under the conditions applied in this study. Several studies have examined the frequency of type 1 and type 3 fimbriae expression in populations of K. pneumoniae strains including strains isolated from the environment (Podschun et al ., 1987;1993;Hornick et al ., 1991;Podschun and Sahly, 1991;Tarkkanen et al ., 1992;Livrelli et al ., 1996). In all studies, the vast majority of strains were found to possess type 1 as well as type 3 fimbriae.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of genes encoding type 1 or type 3 fimbriae was performed by dot-blotting using radiolabelled DNA probes as described previously (Livrelli et al, 1996).…”
Section: Detection Of Adhesin Genesmentioning
confidence: 99%
“…1993). P. aeruginosa accounts for a significant proportion of nosocomial infections and the tendency of nosocomial pathogens to develop or acquire new antibiotic resistance traits poses a great problem in their treatment and control (Livrelli et al. 1996).…”
Section: Introductionmentioning
confidence: 99%